Deixis in Joe Biden’s Speech Inaguration - Marlinda Marlinda; Dias Andris Susanto (Lembaga Penelitian Universitas Swadaya Gunung Djati Cirebon, Indonesia, 2022)
The objective of this study is to identify the kinds of deixes behind the inauguration address of President Joe Biden and to identify the significance of them are shown in the most prevalent deictic words in the Inaugural Speech of Joe Biden. In addition, The study investigates the contribution this research provides to pragmatics teaching. Descriptive qualitative method was employed for data analysis, because it examines the various kinds of deixis seen in this speech. The researchers have written the speech into script, analyzed the deixis utilized, identified the type of deixis, and figure out the deixis contributions in pragmatics class. The findings revealed that three deixis, namely personal, spatial, and temporal deixis were identified in the inauguration address of Joe Biden; Personal deixis (67% data), spatial deixis (21% data) temporal deixis (12% data). After analyzing the three types of deixis in the speech of Joe Biden, the researchers has concluded that in first person deixis the term we become the most commonly used. As President of the United States, he represents the people of the United States in carrying out specified tasks and taking measures that benefit the country. The explanations of deixis also indicated that personal deixis was the most significant type to be found in Joe Biden’s speech inauguration. This research can be utilized by lecturers in particular in the deixis field as teaching material on pragmatics. The research is intended to inform students of the fact that analysis of pragmatics is a solution for those who take a lesson in university Tujuan studi ini adalah untuk mengidentifikasi jenis-jenis deiksis di balik pidato pelantikan presiden Joe Biden serta mengidentifikasi makna penting yang diperlihatkan dalam kata-kata paling umum dalam pidato pelantikan Joe Biden. Selain itu, dalam studi ini bertujuan untuk mengidentifikasi kontribusi dalam penelitian ini terkait pengajaran pragmatis. Metode deskriptif kualitatif digunakan untuk menganalisis data, karena dalam studi ini mengamati beberapa jenis-jenis deixis dalam pidato tersebut. Peneliti telah menulis pidato kedalam naskah, menganalisis deiksis yang muncul, mengidentifikasi jenis deiksis, dan menemukan kontribusi dalam kelas pragmatik. Hasil dari penelitian ini memperlihatkan bahwa terdapat tiga jenis deiksis; personal, spatial, temporal yang telah diidentifikasi. Sebanyak 67% personal deiksis, 21% spatial deiksis, dan 12% temporal deiksis. Setelah menganalisis ketiga tipe deiksis dari pidato Joe Biden, peneliti menyimpulkan bahwa dalam personal deiksis, kata we menjadi kata yang sering dipakai. Sebagai presiden Amerika Serikat, Joe Biden mewakili rakyat Amerika Serikat dalam melaksanakan tugas-tugas tertentu dan mengambil Langkah-langkah yang menguntungkan negara. Penjelasan mengenai deiksis juga menunjukkan bahwa personal deiksis adalah jenis yang paling penting dalam penyajian pidato oleh Joe Biden. Penelitian ini dapat digunakan oleh para dosen khususnya di bidang deiksis sebagai bahan pengajaran atas pragmatics. Penelitian ini dimaksudkan untuk menginformasikan siswa sebuah fakta bahwa analisis pragmatik adalah sebuah solusi bagi mereka yang mengambil pelajaran di universitas